2023
DOI: 10.3390/foods12132567
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Protein and High-Dietary-Fibre Vegetable Processing Waste from Bell Pepper and Tomato for Pasta Fortification

Abstract: There is worldwide wastage of 1.3 billion tons of food annually. It is recommended that food waste should be reduced at every phase of production. By-products from food processing have high nutritional value so their use in new products is advisable. The aim of the study was to enrich the nutritional value of pasta using waste from the food industry. By-products from tomato processing (tomato waste—TW) and pepper (defatted pepper seeds—DPS, pepper placenta—PP) were used at a level of 10–30% to produce pasta. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…These studies also demonstrated an increase in the content of individual fiber fractions, especially SDF, with up to a 2.5-fold increase in trials with a 15% addition of flax materials compared to the control. This is a highly beneficial change, as SDF is often deficient in human diets [162]. In the studies by Wirkijowska et al [17], the IDF:SDF ratio ranged from 1.79:1 for the control to as low as 0.95:1 for a 15% addition of flaxseed cake.…”
Section: Materials and Level Of Supplementation Effects Referencementioning
confidence: 99%
“…These studies also demonstrated an increase in the content of individual fiber fractions, especially SDF, with up to a 2.5-fold increase in trials with a 15% addition of flax materials compared to the control. This is a highly beneficial change, as SDF is often deficient in human diets [162]. In the studies by Wirkijowska et al [17], the IDF:SDF ratio ranged from 1.79:1 for the control to as low as 0.95:1 for a 15% addition of flaxseed cake.…”
Section: Materials and Level Of Supplementation Effects Referencementioning
confidence: 99%
“…Dietary fibers can cause steric hindrance in the viscoelastic network, affecting the integrity and tenacity of the protein-starch network, which can lead to an increase in leached solids, impacting cooking time, weight gain, color changes, and flavor alterations, which are all critical aspects of quality control. Additionally, texture parameters must be maintained, as consumers prefer pasta to remain intact and firm after cooking, achieving the desired "al dente" texture [15,16]. The texture characteristics of pasta dough can play a crucial role in determining final consumer acceptance, indicating a preference for pastas that maintain their texture characteristics after cooking.…”
Section: Introductionmentioning
confidence: 99%
“…One potential source of by-products that can be used to modify food product recipes is vegetable processing waste, specifically tomato by-products (TP) and bell pepper byproducts (PB). These by-products have been studied for their potential applications in various food products, contributing to reducing food waste and enhancing the nutritional value of food [7][8][9]. Previous research has shown that TP can be a good source of dietary fiber, with an approximate content of 61% on a dry basis, while PB has a dietary fiber content of approximately 33% on a dry matter basis [9].…”
Section: Introductionmentioning
confidence: 99%
“…These by-products have been studied for their potential applications in various food products, contributing to reducing food waste and enhancing the nutritional value of food [7][8][9]. Previous research has shown that TP can be a good source of dietary fiber, with an approximate content of 61% on a dry basis, while PB has a dietary fiber content of approximately 33% on a dry matter basis [9]. Additionally, dried tomato waste, including seeds and skin, contains approximately 17-23% protein, and the placenta of bell peppers has a protein content of about 28% [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation